Workshop Pengembangan Media Pembelajaran Berbentuk Komik Berbasis Artificial Intelligence (AI) Pada Calon Guru SD - Muhammad Syazali; Mohammad Irawan Zain; Lalu Hamdian Affandi; Ibrahim Ibrahim; Gita Prima Putra; Ni Made Yeni Suranti; Lalu Wira Zain Amrullah (Indonesian Publication Center, 2025)
The results of a preliminary study conducted through a survey of 104 respondents showed that the majority of them (90.4%) had never developed comic-based media. This was due to difficulties in writing the story script (26%), creating character illustrations (74%), and combining story writing with illustration (12%). A total of 65% encountered obstacles in scriptwriting, 35% faced difficulties in drawing, and 10% experienced challenges in both areas. Therefore, we organized an activity entitled “Workshop on the Development of Comic-Based Learning Media Using Artificial Intelligence (AI) for Prospective Primary School Teachers.” The methods applied in this activity included a combination of lectures, Q&A sessions, demonstrations, and hands-on practice in developing AI-based comic media. The goal of this community service activity was to improve the knowledge and skills of prospective primary school teachers in developing AI-based comic learning media. The workshop, held on July 20, 2024, was carried out smoothly. The participants consisted of 23 students from the PGMI Program at UIN Mataram, with 65.2% female and 34.8% male. Based on their academic year, 13.04% were first-year students, 30.43% were second-year students, and 56.52% were third-year students. The workshop, conducted through presentations and demonstrations, successfully enhanced participants' knowledge and skills in developing AI-based comic learning media.